Identification of nematode worm eggs in children - Nuril Sofiantin (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Intestinal nematodes are a group of parasitic worms that cause helminth infections. About 24℅ of the world's population is infected with worms. Worm infections are infections that are common and found in children. Factors that can cause the risk of worm infections in children are low levels of personal sanitation (clean and healthy living behavior). Helminthiasis is transmitted through soil, either through direct contact or through intermediaries such as food, soil or food contaminated with worm eggs which can spread to children when they play and do not wash their hands before eating. The aim of this research is to determine whether there is intestinal nematode worm egg infection in the feces of children living in the Antang area of Makassar City. This type of research is descriptive using 10 stool samples which are then examined using the native method (direct slide). The results of this study showed that 10 samples examined did not find intestinal nematode eggs or were negative. The role of parents in the health of their children is very important.